SHALE AS HYDROCARBON RESERVOIRS - Adi Junira; Andy Setyo Wibowo (Scientific Contributions Oil and Gas, 2016)
Nowadays, shale plays a role as hydrocarbon producing rock. Due to its “unusual” properties as a reservoir, shale is classified as an unconventional reservoir. Among these properties are the relatively low permeability (0.1 mD or less) and the relatively low porosity (10% or less). The relatively low permeability had been the main obstacle to extracting the hydrocarbon held by shale in the past. Nevertheless, the technologies of horizontal drilling and hydraulic fracturing have proven to be effective in stimulating a liquid flow in low permeability reservoirs such as a shale layer which has encouraged the hydrocarbon exploration in the oil shale industry. This paper is intended to provide an overview of technologies implemented in the current oil shale reservoir along with their challenges summarized from available sources in a concise manner.